Marcas espaciais do tempo histórico: as rugosidades da paisagem rural de Cachoeira do Sul/RS - Conceição, Lisane Regina Vidal (2018)
The research aimed to identify the space and time the Constitution of the roughness in the countryside of municipality of Cachoeira do Sul/RS. For the realization of research, were used the methodological contributions based on historical materialism, dialectical method and qualitative approach, as well as the documentary research and research, using the field journal and application of semi-structured interviews, in order to understand the object of study in your complexity, concurrency of your space and time. The roughness is what is passed as form, landscape, like space built. Represent the materialization of a unique combination of technique, labour and capital in the form created in the landscape in different formations, sociospatial, make possible to understand the space as a product of human action, along its story. The roughness in the countryside of Cachoeira do Sul represents the complexity of rural areas, which were created in different historical periods in accordance with the needs of production and reproduction of social groups. Were listed three types of roughness in the municipality: the roughness of the System of Movement of Merchandise and People that includes the bridges, railway road, port, ferries, telephone station, gas station and post office; the roughness of the Production system comprising offices, farms, plantations, farm where salted and sliced beef is produced, immersion bath for cattle; and the Social Interaction System comprising the old houses, schools, churches, ballroom, abandoned places and family cemeteries. Most of the roughness of the Circulation system is located in the northern of the municipality, on the left of the Jacuí River, as a result of the proximity to the city and the need for access and connection with other regions of the State. These represent the means of roughness as a social group circulates about space and which places keep relationship of production and reproduction. Most of the roughness Production System is located in the northern portion of the municipality, but the presence of the resorts, farms is located in the southern, this fact runs from the different types of occupation and settlement of Cachoeira do Sul, for example, North directed settlement characterized by family farming and South presence of lands characterized by agriculture. These roughnesses represent a necessary condition for human life as it is by producing the man creates space for him to reproduce and repeat. The roughness of the system of Social interaction also predominate in the northern of the city, characterized by colonization. They represent the emotional relationships, symbolic and religious groups. The roughness must be understood as a means to enable resignifications and not as obstacles to socio-economic development of the place. Its concrete presence enhances the space and its resignification allows to the social groups new sources, of permanence in the rural areas, contributing to your production and reproduction as well as to preserve it from oblivion and safeguard in memory the Roughness of the Rural Landscape of Cachoeira do Sul.